Reward: the relationship with employees’ satisfaction at MODENAS Gurun, Kedah / Siti Meryam Dali and Khairunisa Zainal - Dali, Siti Meryam; Zainal, Khairunisa (2010)
The purpose of this study is to identify the relationship between reward and employees’ satisfaction at MODENAS Gurun, Kedah. Reward can be classified into three types which are direct-financial reward, indirect-financial reward, and non-financial reward. However, this study only focuses on several rewards for each type. Rewards that will be studied in this research are performance-based pay, bonus, recognition, promotion and health insurance that has become the independent variables. The dependent variable of this research is employees’ satisfaction. This study will cover the employees of MODENAS Gurun Kedah whereby the sample size will be 72 employees.